Determinants of Foreign News in Nigerian Newspapers - Ajaegbu, Oguchi O.; Sodeinde, Oluwaseyi Adewunmi; Nwogwugwu, Daniel Ikesinachi (NIU Journal of Social Sciences, 2022)
Every day, media professionals are saddled with the responsibility of determining and selecting news that makes it into the news bulletin. This results from limited space and time to consider the teeming number of reports on happenings. While several studies have examined the determinants of news, there is limited knowledge of the determinants of foreign news coverage in Nigerian newspapers. Therefore, this study investigates the determinants of news value of foreign news coverage among Nigerian newspapers to understand the most prominent news values published. The study was anchored on the gatekeeping and news value theory and content analysis method was employed as the methodology. The Vanguard and the Nigerian Tribune constituted the sample for this study and 2021 was the study year. Using Harcup and O’Neil’s (2016) revisited taxonomy of news values, foreign news reports of the selected newspapers were analysed. Findings showed that majority of the reports were in straight news format and most were on sports. Further findings show that the reports had an average of …. News values. This study concludes that newspaper organizations publish foreign reports based on availability and not necessarily any news criteria. Keywords: Gatekeeping theory, Harcup and O’Neill, News determinants, News values, Nigerian Newspapers, journalists.